2019
DOI: 10.3390/su11174667
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Industrial Park (EIP) Development in Viet Nam: Results and Key Insights from UNIDO’s EIP Project (2014–2019)

Abstract: Industrial parks have been promoted as cornerstone strategies for economic development in countries around the world, including Viet Nam. The transformation of conventional industrial zones (IZs) into eco-industrial parks (EIPs) presents an effective opportunity to attain inclusive and sustainable industrial development, as well as increasing the economic competitiveness and resilience of industrial parks. This paper presents and discusses the interventions, key results, and lessons learned from the Ministry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…This development has resulted in the rising consumption of fossil fuel resources especially by the export-oriented industries, and complemented by services and commercial activities (Van and Sam 2008). More recently, governmental efforts on transforming industrial parks into eco-industrial parks have also been reported (Stucki et al 2019). Nonetheless, the results highlight that increasing reliance on fossil resources has been largely responsible for much of the carbon emissions, and its impact share may continue to grow unless adequate policy interventions are implemented.…”
Section: Drivers Of Co 2 Emissions and Their Coefficientsmentioning
confidence: 99%
See 2 more Smart Citations
“…This development has resulted in the rising consumption of fossil fuel resources especially by the export-oriented industries, and complemented by services and commercial activities (Van and Sam 2008). More recently, governmental efforts on transforming industrial parks into eco-industrial parks have also been reported (Stucki et al 2019). Nonetheless, the results highlight that increasing reliance on fossil resources has been largely responsible for much of the carbon emissions, and its impact share may continue to grow unless adequate policy interventions are implemented.…”
Section: Drivers Of Co 2 Emissions and Their Coefficientsmentioning
confidence: 99%
“…This is reflected by the lower impact of the technological factors on CO 2 emissions even after decades of industrial development in the country. Thus, sustainable industrial policies to promote eco-industrial development could also help mitigate industrial CO 2 emissions (Stucki et al 2019;Van Nguyen and Le 2020;Shah et al 2020a).…”
Section: Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, UNIDO has run EIP programs in various countries including Thailand, India, Morocco [11], and South Africa [12]. Especially, an EIP national project has been implemented in Vietnam, funded by the Global Environment Facility (GEF) and the State Secretariat for Economic Affairs of Switzerland (SECO) [13].…”
mentioning
confidence: 99%
“…When it comes to resource, environmental, and savings metrics, knowledge of Vietnam's EIP performance has been limited by the analyses [10,13]. These investigations have lacked consideration and assessment based on mathematical methods, resulting in unsystematic and disconnected outcomes [16,17].…”
mentioning
confidence: 99%